Does a Reduced Secondary Operation Rate Offset Higher Implant Charges when Utilizing Suture Button Fixation for Syndesmotic Injuries?. Issue 2 (February 2023) - Flanagan, Christopher D.; Solomon, Eric; Michalski, Joseph; Stang, Thomas S.; Stenquist, Derek S.; Donohue, David; Shah, Anjan; Maxson, Benjamin; Watson, David; Ochenjele, George; Mir, Hassan R.
Abstract : Objective: To determine whether a reduced secondary operation rate offsets higher implant charges when using suture button fixation for syndesmotic injuries. Design: Retrospective cohort study. Setting: Single, urban, Level 1 trauma center. Participants: Three-hundred twenty-seven (N = 327) skeletally mature patients with rotational ankle fractures (OTA/AO type 44) necessitating concurrent syndesmotic fixation. Intervention: Suture button or solid 3.5-mm screw syndesmotic fixation. Main Outcome Measurements: To compare implant charges with secondary operation charges based on differential implant removal rates between screws and suture buttons. Results: Patients undergoing screw fixation were older (48.8 vs. 39.6 years, P < 0.01), had more ground-level fall mechanisms (59.3% vs. 51.1%, P = 0.026), and sustained fewer 44C type injuries (34.7% vs. 56.8%, P = 0.01). Implant removal occurred at a higher rate in the screw fixation group (17.6% vs. 5.7%, P = 0.005). Binomial logistic regression identified nonsmoker status (B = 1.03, P = 0.04) and implant type (B = 1.41, P = 0.008) as factors associated with implant removal. Adjusting for age, the NNT with a suture button construct to prevent one implant removal operation was 9, with mean resulting additional implant charges of $9747 ($1083/case). Backward calculations using data from previous large studies estimated secondary operation charges at approximately $14220, suggesting a potential 31.5% cost savings for suture buttons when considering reduced secondary operation rates. Conclusions: A reduced secondary operation rate may offset increased implant charges for suture button syndesmotic fixation when considering institutional implant removal rates for operations occurring in tertiary care settings. Given these offsetting charges, surgeons should use the syndesmotic fixation strategy they deem most appropriate in their practice setting. Level of Evidence: Economic Level IV. See Instructions for Authors for a complete description of levels of evidence.